PERANAN PERBANKAN PADA PENERAPAN GREEN BUSINESS DAN SUSTAINABILITY DEVELOPMENT - Diky Rahmansyah; Muhammad Iqbal fasa; Suharto (Jurnal Dinamika Ekonomi Syariah, 2023)
Various things related to greening are increasingly becoming a trend in society. Starting from green labels, green products, green packaging, green consumers, green business, green banking, and so on. All of this is closely related to environmental management issues that have become market demands for environmental safety and sustainability. The greening movement is also happening in banking with the terminology "green banking."Green banking is an activity that mainly leads to sustainability, namely by making environmental protection efforts by promoting a green environment (sustainability) and social investment responsibility. Support from the banking industry through green banking, in actively contributing to environmental protection and management efforts needs to be followed up by preparing legal instruments, providing information, organizing education and socialization, and joint research.